An Architecture for a Brain-Image Database - Herskovits, E. H. (Methods of Information in Medicine, 2000)
The widespread availability of methods for noninvasive assessment of brain structure has enabled researchers to investigate neuroimaging correlates of normal aging, cerebrovascular disease, and other processes; we designate such studies as image-based clinical trials (IBCTs). We propose an architecture for a brain-image database, which integrates image processing and statistical operators, and thus supports the implementation and analysis of IBCTs. The implementation of this architecture is described and results from the analysis of image and clinical data from two IBCTs are presented. We expect that systems such as this will play a central role in the management and analysis of complex research data sets.
Keywords: Statistical Analysis; Brain; Magnetic Resonance; Images; Analysis; Image Display